Airborne Radioiodine Contamination Caused by 131I Treatment* - Krześniak, J. W.; Chomicki, O. A.; Czerminska, M.; Górowski, T. (Nuklearmedizin - NuclearMedicine, 1979)
Estimation of exposure from 131I inhaled from unsealed sources during laboratory procedures and from that exhaled by patients treated with 131I has revealed that the permissible levels have been exceeded by a factor of 2 - 5, although the absorbed activity was found to be between 1 and 10% of the maximum permissible absorption of 13'I inhaled through the lungs. The fall in 131I concentration in the air exhaled by 19 hyperthyroid patients, to whom 131I was administered in a dose of several hundred MBq, could be expressed by a two-component equation, which reflects the changes in 131I concentration in the blood.